Secondary Metabolites in Ramalina terebrata Detected by UHPLC/ESI/MS/MS and Identification of Parietin as Tau Protein Inhibitor - Cornejo, A.; Salgado, F.; Caballero, J.; Vargas, R.; Simirgiotis, M.; Areche, C. (International Journal of Molecular Sciences, 2016)
Indexación: Web of Science. Liquid chromatography coupled with mass spectrometry is an outstanding methodology for fast analysis of phenolic compounds in biological samples. Twenty two compounds were quickly and accurately identified in the methanolic extract of the Antarctic lichen Ramalina terebrata for the first time using ultra high pressure liquid chromatography coupled with photodiode array detector and high resolution mass spectrometry (UHPLC-PDA-Q/Orbitrap/MS/MS). In addition, the extract and the four compounds isolated from this species were tested for the inhibitory activity of tau protein aggregation, which is a protein involved in Alzheimer's disease (AD). All compounds showed null activity with the exception of parietin, which it was able to inhibit aggregation process of tau in a concentration range between 3 mu g/mL (10 mu M) to 28 mu g/mL (100 mu M). In addition, we show how parietin interact with tau (306)VQIVYK(311) hexapeptide inside of the microtubule binding domain (4R) with the help of molecular docking experiments. Finally, the constituents present in the methanolic extract could possibly contribute to the established anti-aggregation activity for this extract and this in-depth analysis of the chemical composition of R. terebrata could guide further research into its medicinal properties and potential uses. http://www.mdpi.com/1422-0067/17/8/1303